Keterbacaan Informasi Naratif Laporan Tahunan dan Cash Holdings - Annisaa Rahman; Rayna Kartika (Jurnal Ilmiah Akuntansi, 2021)
This research aims to test and analyze the effect of readability narrative information of the annual report on cash holdings.  The readability is measured by the Gunning Fog Index, while cash holdings are measured by the ratio of cash to total assets. The study was conducted in the period 2015 to 2017. The population of this study is all non financial sector companies listed on the Indonesia Stock Exchange. Sampling techniques used purposive sampling and selected 712 firm-year. Data analysis uses multiple linear regressions. The results show that the readability of the company's annual report affects the companies’ cash holdings. The harder the annual report is read, the greater the amount of cash held by the company. The findings of this study are in line with precautionary and agency motives. The findings of this study briefly show support for the readability of annual reports on the company's internal financial policies.